Estimation of Watershed Runoff through Geomorphological Parameters - Sahoo, N.; Rajput, T.B.S.; Rao, A.R.; Bhattacharya, A.K. (Journal of Soil and Water Conservation, 2022)
Twenty-two numbers of geomorphological parameters were quantified for each watershed using toposhect information and standard formulae available in the Handbook of Applied Hydrology written by Ven Te Chow. It was fount that the geomorphological parameters of all the eleven watersheds are very much correlated among themselves. Simple multiple regression technique could not be applied to establish a valid relationship between runoff as dependent variable and geomorphological parameters as independent variables. This problem was addressed by adopting the technique of "Principal Component Analysis" to transform the original set of variables into a new set of uncorrelated variables called Principal Components. The principal components were again converted into scores of principles components. The statistically significant runoff models were developed taking runoff as dependent variable and scores of principal components as independent variables using principal component regression in the environment of Statistical Analysis System. The developed runoff models were meaningfully discussed in terms of physical geomorphological parameters to make them widely applicable